Evaluasi Kemantapan Permukaan Jalan Berdasarkan International Roughness Index Pada 14 Ruas Jalan di Kota Yogyakarta - Ardilson Pembuain; Sigit Priyanto; Latif Budi Suparma (TEKNIK, 2018)
Roads that have poor surface roughness can cause uncomfortable to road users, traffic accidents, increase dynamic loads on the road surface, thereby accelerating the process of road damage, and damage to vehicles. This research aims to evaluate the stability of road conditions based on the international roughness index (IRI). Evaluation of road stability conditions was carried out on 14 road segments in the city of Yogyakarta, with details of four secondary arterial road segments and 10 secondary collector road segments. Data on road surface roughness (IRI) values were obtained using NAASRA roughness meter which refers to SNI 03-3426-1994. Evaluation of the stability of road conditions is done by comparing the IRI values of the survey results and the limits of IRI values determined by the Directorate General of Highways. The results showed that 14 roads were evaluated, 64% were in moderate condition and 36% were in good condition. Of the 14 roads, the Sisingamangaraja, Lowanu, and Sugeng Jeroni roads have the highest IRI value in a sequence so that the three road segments are prioritized for handling.